2010
DOI: 10.1098/rsbl.2010.0456
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi reduce leaf-cutting ant damage to seedlings

Abstract: Our study examines how the mutualism between Atta colombica leaf-cutting ants and their cultivated fungus is influenced by the presence of diverse foliar endophytic fungi (endophytes) at high densities in tropical leaf tissues. We conducted laboratory choice trials in which ant colonies chose between Cordia alliodora seedlings with high (E high ) or low (E low ) densities of endophytes. The E high seedlings contained 5.5 times higher endophyte content and a greater diversity of fungal morphospecies than the E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 14 publications
(18 reference statements)
4
44
0
Order By: Relevance
“…A previous study showed that leaf-cutting ants prefer to cut leaves with low rather than high colonization by endophytic fungi (Bittleston et al, 2011). Here we show that changes in the chemical characteristics of leaves resulting from their symbiosis with leaf endophytes are associated with most of the observed ant preferences.…”
Section: Discussionsupporting
confidence: 59%
“…A previous study showed that leaf-cutting ants prefer to cut leaves with low rather than high colonization by endophytic fungi (Bittleston et al, 2011). Here we show that changes in the chemical characteristics of leaves resulting from their symbiosis with leaf endophytes are associated with most of the observed ant preferences.…”
Section: Discussionsupporting
confidence: 59%
“…Molecular techniques have greatly increased knowledge of microbial diversity and functions. For example, we now know that gut bacteria influence human weight, nutrition, and immune function [24]; bacterial and yeast endosymbionts provide insects with nutrition and protection (reviewed in [25]); and fungal endophytes deter plant pathogens and herbivores [26][27][28]. However, the majority of the world's microbes-and their interactions and functionsremain difficult to characterize.…”
Section: Examples Of Convergent Interactionsmentioning
confidence: 99%
“…Endophytic fungus on plant leaves can also reduce the foraging and processing efficacy of leaf-cutting ants [101,102] probably because of low volatility compounds released after their wounding [103].…”
Section: Biological Controlmentioning
confidence: 99%